CEREBELLAR TRANSCRANIAL DIRECT CURRENT STIMULATION AND GAIT TRAINING IN CHILDREN WITH DOWN SYNDROME: A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED CLINICAL TRIAL - Silva, Marcele Paganoto Garcia Rodrigues da; Silva, Paula Soares da; Silva, Sara Viana de Abreu; Oliveira, Caroline Priscila de; Souza, Amanda Macedo de F.; Ferreira, Giselle Araujo; Silva, Rafael dos Anjos; Araújo, Marcela de Oliveira; Collange, Luanda André (CIPEEX, 2025)
The objective of this research project is to compare the effects of ten sessions of treadmill training combined with active cerebellar transcranial direct current stimulation (tDCSa) and placebo on the Activity (mobility and functional balance) and Participation domains of the ICF of children with Down syndrome (DS). This is a randomized, placebo-controlled, double-blind clinical trial involving 30 children diagnosed with DS, aged between 3 and 8 years, who meet the eligibility criteria. Participants will be assessed one week before, one week and one month after the end of the intervention, using the Timed Up and Go, 10-meter walk test, Pediatric Balance Scale, and Measure of Participation and Environment - Children and Youth. The experimental group will perform treadmill training combined with active cerebellar tDCSa application. The control group will perform treadmill training combined with placebo tDCS application. The speed of the gait training will be established according to the child's performance in each session. tDCS will be applied with the anode electrode positioned over the cerebellar region and the cathode electrode over the central supraorbital region. The intervention will consist of ten sessions, with a frequency of five sessions per week, conducted over two consecutive weeks, each lasting 20 minutes. Considering the potential effect of cerebellar tDCSa, it is expected that the intervention will enhance the effect size of treadmill training in children with DS.